Strategies for optimizing mangrove ecosystem management in the rehabilitation area of Sayung coastal zone, Demak Regency, Central Java - Handayani, Setyo; Adrianto, Luky; Nurjaya, I Wayan; Bengen, Dietriech G; Wardiatno, Yusli (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Sayung coast is experienced very high coastal erosion and has a huge impact on the lives of the surrounding communities. One of the efforts in handling coastal erosion is the rehabilitation of the mangrove ecosystem.The purpose of this study was to prioritize mangrove ecosystem management strategies in rehabilitation areas. Data were collected from three coastal villages, namely, Bedono, Timbulsloko, and Surodadi, through in-depth interviews, questionnaires, and field observations. The data analysis was carried out using the Analytical Network Process (ANP) method. The result showed that the priority problems in the mangrove ecosystem management on the Sayung coast were: conversion of mangrove land, failure of mangroves to grow, lack of monitoring and supervision. Therefore, the priority solution for optimizing mangrove ecosystem management is rehabilitation and conservation, increasing community participation, and monitoring by involving the community.